2005
DOI: 10.1111/j.1745-7262.2005.00046.x
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of risk factors for male infertility in Nigeria

Abstract: INFERTILITY is associated with various proxies of sexually transmitted infections (STIs) and poor healthcare-seeking behavior for STIs in Nigerian men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 7 publications
6
34
2
1
Order By: Relevance
“…[1,3,6,12,20] Environmental factors such as exposure to heat and chemicals, lifestyle factors such as smoking and alcohol consumption, chronic medical conditions such as diabetes mellitus and thyroid disease, previous groin surgery, including herniorrhaphy or varicocelectomy, and past mumps infection have been demonstrated as having adverse effects on sperm parameters. [12,23] Consistent with previous reports, [24][25][26] this study demonstrated a significant association between smoking habit, past infection with mumps (mumps orchitis) and past groin surgery and abnormal sperm parameters, although Okonofua et al [26] also reported a significant association with alcohol consumption, among other factors.…”
Section: Discussionsupporting
confidence: 81%
“…[1,3,6,12,20] Environmental factors such as exposure to heat and chemicals, lifestyle factors such as smoking and alcohol consumption, chronic medical conditions such as diabetes mellitus and thyroid disease, previous groin surgery, including herniorrhaphy or varicocelectomy, and past mumps infection have been demonstrated as having adverse effects on sperm parameters. [12,23] Consistent with previous reports, [24][25][26] this study demonstrated a significant association between smoking habit, past infection with mumps (mumps orchitis) and past groin surgery and abnormal sperm parameters, although Okonofua et al [26] also reported a significant association with alcohol consumption, among other factors.…”
Section: Discussionsupporting
confidence: 81%
“…Present study recorded significantly decreased sperm quality in infertile men was compared to fertile, concordant to studies of [24,25,26] Lipid peroxidation of sperm membrane is considered to be the key mechanism of ROS induced sperm damage. MDA is byproduct of lipid peroxidation and important marker for oxidative stress.…”
Section: A Comparison Of Age Semen Parameters and Mda Between Fertilsupporting
confidence: 69%
“…The degree of infertility and its cause vary from place to place. These are evident from the study pursued in mid-Western Nigeria which brought to the lime light that about 50%, of the 780 couples under evaluation, differed in the causes of their infertility 41 . Study associated with South-Western Nigeria reported that 42.4% infertility resulted from the male factor 42 .…”
Section: Data Extraction and Data Anaysismentioning
confidence: 99%